1968
DOI: 10.1083/jcb.37.3.729
|View full text |Cite
|
Sign up to set email alerts
|

Membranes of Animal Cells

Abstract: Turnover studies of the surface membrane and of cell particulate matter of L cells in tissue culture in logarithmic and plateau phase of growth have been made. The rate of incorporation of isotope into these fractions and the rate of fall of specific activities of labeled L-cell fractions have been observed. The following interpretation of the data appears most likely although other interpretations are possible. Growing and nongrowing cells synthesize approximately similar amounts of surface membrane and parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0

Year Published

1971
1971
1979
1979

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(58 citation statements)
references
References 46 publications
5
53
0
Order By: Relevance
“…Studies of the metabolism of the surface membrane molecules have shown a continuous cell surface turnover and release of substances into the surrounding medium (Warren and Glick, 1968). Our studies appear to indicate that the local immune reactions increase this cell surface turnover and subsequent release.…”
Section: Discussionsupporting
confidence: 55%
“…Studies of the metabolism of the surface membrane molecules have shown a continuous cell surface turnover and release of substances into the surrounding medium (Warren and Glick, 1968). Our studies appear to indicate that the local immune reactions increase this cell surface turnover and subsequent release.…”
Section: Discussionsupporting
confidence: 55%
“…L-cell membrane turnover was studied using a number of different internal labels, [l~C]leucine, [l'C]glucosamine, and [~4C]glucose (33). The last label is rather nonspecific and no attempt was made to identify the species labeled.…”
Section: Other Studies Of Membrane Protein Turnovermentioning
confidence: 99%
“…Different techniques have been used (3,4,8,17,20,25,33) but most suffer from the necessity of isolating membranes of varying purity and yield as well as the problem of reutilization of label. Use of the enzymatic iodination technique to label only the externally disposed membrane proteins provided a reasonable solution to both problems.…”
mentioning
confidence: 99%
“…Likewise, we do not know whether the other membrane proteins are also turning over, but at a rate too slow to be seen in our experiments. It should be noted that there is extensive turnover of membranes in cultured mammalian cells, even when they are in a stationary, nongrowing state (36).…”
Section: Proteins Synthesized By Intact Reticulocytesmentioning
confidence: 99%